Monitoring of Moisture and Dimensional Behaviors of Nail-Laminated Timber (NLT)-Concrete Slab Exposed to Outdoor Air - HWANG, Sung-Wook; CHUNG, Hyunwoo; LEE, Taekyeong; AHN, Kyung-Sun; PANG, Sung-Jun; BANG, Junsik; KWAK, Hyo Won; OH, Jung-Kwon; YEO, Hwanmyeong (Journal of the Korean Wood Science and Technology, 2022)
The moisture and dimensional behaviors of a nail-laminated timber (NLT)–concrete slab composed of an NLT–plywood composite and topping concrete are monitored for 385 days. The slab is developed for using as flexural elements such as floors. The humidity control of wood gently introduces significant fluctuations under the ambient relative humidity into the slab, and fluctuations in the relative humidity result in dimensional changes. The equilibrium moisture content of the slab increases from 6.7% to 15.3% during the monitoring period, resulting in a width (radial) strain of 0.58%. The length (longitudinal) strain is negligible, and the height (tangential) strain is excluded from the analysis because of abstruse signal patterns generated. Concrete pouring causes a permanent increase in the width of the NLT–plywood composite. However, the width deforms because the weight of the concrete mixture loosens the nail-laminated structure, not because of the significant amount of moisture in the mixture. The dimensional stabilization effect of the nail-laminated system is demonstrated as the composite strain is lower than the total strain of lumber and plywood, which are elements constituting the nail-laminated structure. KCI Citation Count: 4